nhiều quá, các bn ngại làm, chia nhỏ ra,mk làm cho 2 câu
a) x2 +5x -6 = x2 -x +x + 5x -6
= x2 -x +6x -6
= x( x-1) + 6(x-1) = (x-1)(x+6)
b) 5x2 +5xy -x-y = 5x(x+y) -(x+y)
= (x+y)(5x-1)
e) \(2x^2+3x-5\)
\(=2x^2+5x-2x-5\)
\(=x\cdot\left(2x+5\right)-\left(2x+5\right)\)
\(=\left(x-1\right)\left(2x+5\right)\)
f) \(16x-5x^2-3\)
\(=-5x^2+16x-3\)
\(=-5x^2+15+x-3\)
\(=-5\cdot\left(x-3\right)+x-3\)
\(=\left(-5x+1\right)\left(x-3\right)\)
c)7x-\(6x^2\)-2
=3x + 4x - \(6x^2\) - 2
=(3x - \(6x^2\)) - (2 - 4x)
= 3x(1 - 2x) - 2(1 - 2x)
=(1-2x)(3x-2)